2022
DOI: 10.12688/wellcomeopenres.17533.1
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic preparedness and responsiveness of research review committees: lessons from review of COVID-19 protocols at KEMRI Wellcome Trust Research Programme in Kenya

Abstract: Background: The scale of the COVID-19 pandemic and novelty of SARS-CoV-2 presented unprecedented challenges in the review of COVID-19 protocols. We investigated how research at the Kenya Medical Research Institute - Wellcome Trust Research Programme (KWTRP) was reviewed, including by institutional and national level committees. Methods: A document review and in-depth interviews with researchers, regulators and research reviewers were conducted. Documents reviewed included research logs of all protocols submitt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 7 publications
(34 citation statements)
references
References 27 publications
(31 reference statements)
0
34
0
Order By: Relevance
“…As shown in Table 3, most (6/9) of the included articles are discussion papers published in peer-reviewed journals [23,[56][57][58][59]61]. Two original research articles were included: a qualitative methods paper [62] and a mixed method paper with a strong qualitative element [52]. Six articles covered issues related to ethics review and EVD considerations [23,56,57,[59][60][61]; three covered issues linked to COVID-19, including (informed) consent [58], stakeholder engagement [62] and research and ethics review [52]; three commented on virtual modalities for review (meetings), consultations or obtaining consent [23,52,58]; and five described review timelines during public health disasters [52,57,[59][60][61].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…As shown in Table 3, most (6/9) of the included articles are discussion papers published in peer-reviewed journals [23,[56][57][58][59]61]. Two original research articles were included: a qualitative methods paper [62] and a mixed method paper with a strong qualitative element [52]. Six articles covered issues related to ethics review and EVD considerations [23,56,57,[59][60][61]; three covered issues linked to COVID-19, including (informed) consent [58], stakeholder engagement [62] and research and ethics review [52]; three commented on virtual modalities for review (meetings), consultations or obtaining consent [23,52,58]; and five described review timelines during public health disasters [52,57,[59][60][61].…”
Section: Resultsmentioning
confidence: 99%
“…These were the countries most affected by EVD between 2014 and 2016. One article drew on South African experience [58] and another on Kenyan experience [52] during the COVID-19 pandemic. The remaining two articles reference Africa broadly [62] or extrapolated from an African experience to make comments about ethics review processes during PHEs across low-and middle-income countries [60].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Several of these contributions focus exclusively on one ERC, usually associated with an academic or health care institution. The literature includes descriptions of ERC operations during the pandemic in Central America and the Dominican Republic [17], China [18], Ecuador [19], Egypt [20], Germany [21], India [2224], Iran [10], Ireland [25], Kenya [26], Kyrgyzstan [27], Latin America [28], the Netherlands [29], Pakistan [30], South Africa [31,32], Turkey [33], and the United States [3436]. Most of these studies reported results from surveys, interviews, focus groups, and documentary analysis, including review of research protocols, ERC meeting minutes, and existing SOPs.…”
Section: Discussionmentioning
confidence: 99%